A FIND OF THE NORTH-CAUCASIAN CERAMICS IN THE ELITE BURIAL OF THE ISAKOVKA I BURIAL GROUND (WESTERN SIBERIA) - Sarapova, Svetlana Vladimirovna; Trufanov, Aleksandr Akovlevic; Kiseleva, Dar'a Vladimirovna; Sagalov, Evgenij Sergeevic; Danilov, Danil Anatol'evic; Hor'kova, Arina Nikolaevna; Okuneva, Tat'ana Gennad'evna; Solosenko, Natalia Gennad'evna; Ranskaa, Anastasia Dmitrievna; Uporova, Natal'a Sergeevna (History, Archeology and Ethnography of the Caucasus, 2022)
We present the results of a multi-disciplinary analysis of a jug and its contents from the elite burial complex of the Sargat culture in Middle Irtysh Basin (burial Isakovka I, mound 3, burial 6). The burial, along with military equipment and various metallic import, contained a ceramic jug, the closest analogies to which are found in the production centers of the settled population of the foothill zone of the central and partially eastern regions of the North Caucasus, as well as the steppe territory (the basin of the Kuma River). The studied piece is distinguished by its massive form and traces of repair of the upper part. The jug was placed in the burial filled with a granular substance with fragments of light and gray-black color. Laboratory analysis found no traces of tartrates, i.e. the jug was not used for cooking or transporting beverages of grape juice. The detected fractions of biogenic apatite could possibly originate from fish bones and scales, used for the production of glue, which was added for clarification of wine, beer and mead. At the same time, the composition of the filling contains organic substances related to the production of a low-alcohol drink based on honey, fermented with the addition of cereal grains (local wild or coming from agricultural centers). There are two versions for defining this drink: either it was beer – one of the oldest ritual drinks, the use of which in pastoral cultures is confirmed by texts of the Nart sagas and is confirmed by similar forms of words of Iranian origin; or an infusion of herbs/cereals based on honey, also common in the ritual practices of ancient and traditional cultures. This find is considered exceptional, since the North Caucasian antiquities of the Early Iron Age have been previously unknown in the forest-steppe monuments of the Trans-Urals and Western Siberia. It is possible that the area of the Sargat culture is so far the easternmost territory of distribution of such ceramics.
Keywords: multi-disciplinary approach; Early Iron Age; Sargat Culture; ancient elite; ceramic import; ritual drink